Understanding the attitudes of paramedics towards suicidal patients - Rant, Barbka (Obzornik zdravstvene nege, 2014)
Introduction: Since it is almost impossible to identify every suicidal person, the timely intervention of an emergency medical team is of the most importance for preventing suicide attempts. Yet its success depends not only on timely help, but also on the treatment of the suicidal individual, the quality of which is to a large degree determined by the attitudes of the paramedics to the suicide. Hence, this article addresses the issue of how Slovenian paramedics experience suicidal patients, or in other words, what their attitudes to suicidal patients are when treating them. Methods: This study is based on a descriptive qualitative method of empirical research, in which inductive analysis has been used. To collect the empirical material, semi-structured interviews with ten paramedics were conducted between December 2012 and January 2013. Results: Despite their professional conduct in working with suicidal patients, Slovenian paramedics often experience various unpleasant emotions while treating them. Although they show understanding, the paramedics are often caught in dilemma while treating suicidal patients, especially those that refuse help or are aggressive. During the treatment, the paramedics act according to their subjective risk assessment and previous work experience, yet they lack the expertise to work with suicidal patients, particularly communication skills. Discussion and conclusion: The attitude of the participants to suicidal patients is based primarily on the emotional aspect of their work. The research showed that a negative attitude may appear, but is not permanent. It appears only in certain conditions when caring for patients who are aggressive or threaten others and when the participants have not received help from other services.
Keywords: emergency medical aid; nasilni pacient; nujna medicinska pomoč; nursing care; samomor; suicide; violent patient; zdravstvena nega